Pengaruh Disiplin Kerja Dan Kompetensi Terhadap Kinerja Guru SMP Negeri 1 Torjun Kabupaten Sampang Melalui Motivasi Sebagai Variabel Intervening - Roni Roni; Ruddy Winarko; Wasis Budiarto (Journal of Management and Creative Business, 2023)
The results showed that: 1) Work discipline has a significant positive effect on teacher performance with an original sample value of 0.260 and a p-value of 0.009. 2) Work discipline has a significant positive effect on motivation with an original sample value of 0.410 and a p-value of 0.024. 3) Competence has a significant positive effect on motivation with an original sample value of 0.470 and a p-value of 0.004. 4) Competence has a negative and insignificant effect on teacher performance with an original sample value of 0.825 and a p-value of -0.042. 5) Motivation has a significant positive effect on teacher performance with an original sample value of 0.611 and a p-value of 0.002. 6) Work discipline has a positive and insignificant effect on teacher performance mediated by motivation with an original sample value of 0.251 and a p-value of 0.107. 7) Competence has a significant positive effect on teacher performance mediated by motivation with an original sample value of 0.287 and a p-value of 0.034.